Seed Collage Game To Improve Children's Fine Motor Skills In The Kasih Bunda Palambayan Playgroups, Agam Regency - Fadli Rambe, Khairul; Wisma, Juliza; Rahmi, Azvi (Journal of Islamic Early Childhood Education, 2024)
Most children are not yet able to complete tasks that involve hand-eye coordination independently, such as sticking, arranging, and drawing. The bean collage activity, which was previously rarely used, is considered to have the potential to be a fun and effective learning medium in developing these skills. The purpose of this study was to determine the planning, implementation, and evaluation of bean collage activities in supporting the development of fine motor skills in children aged 4–6 years at the Kasih Bunda Playgroup, including analyzing the factors that support and hinder its implementation. The results of the study showed that: (1) The planning of the collage activity was carried out systematically by considering the learning theme, the child's developmental level, and the availability of safe and interesting materials, (2) The implementation of the activity took place in a fun and interactive atmosphere, where children showed high enthusiasm and gradual improvement in fine motor skills, (3) Evaluation was carried out through direct observation, documentation of work results, and teacher reflection, and showed that the collage activity contributed positively to the coordination, accuracy, and independence aspects of children. Supporting factors included adequate facilities, support from the principal, teacher and parent involvement, while inhibiting factors included limited materials, safety risks, and inconsistent child participation.